Intermolecular interaction in liquid crystals - Agelmenev, M.E. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The analysis of possible mechanisms for the implementation of orientational ordering in the mesophase of liquid crystals has been carried out. It has been shown that benzene rings in the structure play a major role in the existence of the mesophase. Van-Vlecky paramagnetism, due to ring currents in benzene rings, seems to be one of the reasons for such ordering. Apparently, this explains the high degree of order of liquid crystals when exposed to a magnetic field. In this regard, the intermolecular interaction in the case of π-staсking may have a magnetic component. A type of possible intermolecular interaction potential is proposed when simulating the behavior of an ensemble of liquid crystal molecules. It is shown that the ordering of molecules of liquid crystals is associated with the different nature of intermolecular interactions, but having the same order.
Keywords: liquid crystals; aromatic compounds; the potential of intermolecular interaction; modeling